Sustainability of Non-Formal Education for Indonesian Migrant Children - Faradila Aini; Nurhafid Ishari; Ahmad Ihwanul Muttaqin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Access to education for Indonesian migrant children in Malaysia remains limited due to immigration restrictions and socio-economic barriers, making non-formal education a vital alternative. Specific Background: The Sentul Guidance Center (Sanggar Bimbingan Sentul) serves as a Community Learning Center (PKBM) under the Indonesian Embassy, providing literacy, numeracy, and religious habituation to children without formal school access. Knowledge Gap: Previous studies have examined program effectiveness but rarely explored long-term sustainability, especially the interplay of institutional support, parental involvement, and spiritual practices. Aims: This study investigates the factors sustaining non-formal education, analyzing how institutional, pedagogical, and community elements ensure continuity despite limited resources. Results: Using a qualitative case study, findings reveal that sustainability depends on embassy-backed institutional support, adaptive teacher strategies, parental moral encouragement, and high student motivation. Religious activities, particularly the duha prayer, enhance discipline and learning focus. Novelty: Unlike prior research, this study highlights the combined influence of state educational diplomacy, collaborative community engagement, and the integration of spiritual practices as critical to program resilience. Implications: The results provide a model for policy development and program design, demonstrating that multi-stakeholder collaboration and the inclusion of spiritual dimensions can sustain non-formal education for migrant children in challenging contexts. Highlights: Institutional and community collaboration ensures program continuity. Adaptive teaching and duha prayer enhance learning discipline. Parental moral support motivates children despite limited involvement. Keywords: Non Formal Education, Migrant Children, Sentul Guidance Center, Calistung, Duha Prayer